Cardioprotective Effects of Kv4.3 on Oxidative Stress in Heart Failure. (25th November 2020) - Wang, Y; Cheng, J
Abstract: Background: Oxidative stress is a pathogenic mediator in heart failure (HF) development, causing excessive Ca2+/calmodulin-dependent kinase II (CaMKII) activation and consequent cardiac dysfunction. We previously reported that Ito channel subunit Kv4.3 couples to CaMKII and inhibits Ca2+-induced CaMKII activation. However, whether Kv4.3 also blocks the oxidation-induced CaMKII activation and the impact on cardiac function in failing heart remain undetermined. Methods and results: Dissociation of Kv4.3 from Kv4.3-CaMKII units by 4-AP incubation or down-regulation of Kv4.3 by transfection with Kv4.3 antisense adenovirus in adult mouse ventricular myocytes enhanced H2O2-induced increase in CaMKII oxidation and autophosphorylation. Co-immunoprecipitation of Kv4.3 with CaMKII, rather than its oxidative or phosphorylated forms, was detected with H2O2 Incubation. Fluorescence spectra assay showed that Kv4.3 binding prevented the transformation of inactive CaMKII to its active conformation in the presence of Ca2+/CaM and H2O2. In pressure-overload HF mice, transfection with Kv4.3 adeno-associated virus (AAV9) had no impact on the content of reactive oxygen species but effectively suppressed CaMKII oxidation and the oxidative CaMKII activation. Importantly, AAV-Kv4.3 transfection led to remarkable improvement in both systolic and diastolic function in failing heart, which is associated with the reduction in ventricular fibrosis, increase in Ca2+ transient and sarcomere shortening in ventricular myocytes with unchanged Ca2+ decline and sarcomere relaxation and preserved myofilament sensitivity to Ca2+. Conclusion: Our results demonstrated that Kv4.3 is an important endogenous regulator that blocks CaMKII oxidation and oxidation-induced CaMKII activation by binding to CaMKII and preventing Ca2+/CaM-induced conformational change. Restoration of Kv4.3 expression improves both systolic and diastolic function, manifesting a promising strategy for HF therapy. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): National Natural Science Foundation of China (NSFC) and National Institutes of Health (NIH) of America